Biodiversidade e padrões de distribuição da anurofauna do Parque nacional das emas e entorno - KOPP, Katia A (2009)
Composition and diversity of anuran amphibians in preserved and disturbed environments in the Cerrado of the State of Goiás, Mid-West Brazil. The Cerrado is the second largest biome of Brazil, with an approximate area of 2 million km², which represents about 23% of the total area of the country. Despite the high conversion of natural areas of the Cerrado in agricultural areas and pastures, comparative studies that address aspects of the composition and diversity of frogs from adjacent areas in different states of conservation are lacking. Thus, this study aimed to address taxonomic richness and community composition of anuran amphibians in twelve water bodies located in preserved areas (inside the National Park of Emas - PNE) and disturbed areas located around the PNE to test whether the structure of frogs communities is different in preserved and disturbed areas and whether species richness is correlated with descriptors of the heterogeneity of habitats. Were recorded 25 species of frogs belonging to nine genera of five families in the 12 water bodies sampled. Species richness was higher in disturbed than in preserved areas. Diversity and equitability were significantly higher in preserved water bodies (P <0.05) while dominance was higher in disturbed water bodies. An analysis of percentage of similarity (SIMPER) showed that the percentage of dissimilarity between the compared groups was 52.26%. The analysis of similarity (ANOSIM) showed significant results on differentiation between groups (Global R = 0.17, P = 0.04). Species richness was not related to any descriptor of heterogeneity. Geographic distance was related to species composition between sampled water bodies (r = -0.35, p = 0.01). At least two non-exclusive factors may be responsible for patterns of species composition and diversity of frogs found in the environments studied: a) the disturbance caused by human action in the use of natural areas for agriculture and livestock enables greater richness of species in disturbed areas, which is consistent with the hypothesis of intermediate disturbance, b) the migration between adjacent ponds allows the maintenance of communities and patterns of species composition. Thus, although species richness was lower in preserved water bodies, the highest diversity recorded in such habitats demonstrates their importance for the maintenance of community integrity and viable frogs populations